cho pt : X^2 -2mx+m^2 -m+1=0.tìm x1^2 + x2^2 =22 30/07/2021 Bởi Skylar cho pt : X^2 -2mx+m^2 -m+1=0.tìm x1^2 + x2^2 =22
Đáp án: $m=3$ Giải thích các bước giải: Ta có $\Delta’=(-m)^2-1\cdot (m^2-m+1)=m-1$ Để phương trình có $2$ nghiệm $\to \Delta’\ge 0$ $\to m-1\ge 0$ $\to m\ge 1$ Khi đó phương trình có $2$ nghiệm $x_1,x_2$ thỏa mãn: $\begin{cases} x_1+x_2=2m\\x_1x_2=m^2-m+1\end{cases}$ Để $x_1^2+x_2^2=22$ $\to (x_1+x_2)^2-2x_1x_2=22$ $\to (2m)^2-2\cdot (m^2-m+1)=22$ $\to 2m^2+2m-24=0$ $\to m^2+m-12=0$ $\to (m-3)(m+4)=0$ $\to m\in\{3,-4\}$ Lại có $m\ge 1\to m=3$ Bình luận
Đáp án: $m=3$
Giải thích các bước giải:
Ta có $\Delta’=(-m)^2-1\cdot (m^2-m+1)=m-1$
Để phương trình có $2$ nghiệm
$\to \Delta’\ge 0$
$\to m-1\ge 0$
$\to m\ge 1$
Khi đó phương trình có $2$ nghiệm $x_1,x_2$ thỏa mãn:
$\begin{cases} x_1+x_2=2m\\x_1x_2=m^2-m+1\end{cases}$
Để $x_1^2+x_2^2=22$
$\to (x_1+x_2)^2-2x_1x_2=22$
$\to (2m)^2-2\cdot (m^2-m+1)=22$
$\to 2m^2+2m-24=0$
$\to m^2+m-12=0$
$\to (m-3)(m+4)=0$
$\to m\in\{3,-4\}$
Lại có $m\ge 1\to m=3$